2017
DOI: 10.1021/acs.analchem.6b03624
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Immune Monitoring: An Automated Immunoassay Platform for Quantification of Blood Biomarkers in Patient Serum within 20 Minutes

Abstract: This Article presents an automated, compact, and self-contained system for sensitive quantitative detection of blood biomarkers. A disposable microfluidic chip, prefilled with biomarker-specific reagents and magnetic beads, can be processed fully automatically by a readout platform, enabling an immunoassay-based analysis with a processing time from sample incubation to signal analysis of 20 min. Novel concepts for on-chip vortexing of the magnetic beads and on-chip reagent storage and actuation were developed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The IMMULITE® system offers sensitive biomarker quantification, including an inflammation panel. The IMMULITE® 1,000 system is a small benchtop immunoanalyzer that is easy to use with a low cost of operation (Zirath et al, 2017 ). Chaemsaithong et al ( 2015 ) compared the concentrations of IL-6 and IP-10 in amniotic fluid determined by standard enzyme-linked immunosorbent assay (ELISA) and a lateral flow-based immunoassay and reported that the results of the POC test strongly correlated with concentrations as determined by ELISA.…”
Section: Alternative Approaches As Potential Diagnostic Avenues For Tmentioning
confidence: 99%
“…The IMMULITE® system offers sensitive biomarker quantification, including an inflammation panel. The IMMULITE® 1,000 system is a small benchtop immunoanalyzer that is easy to use with a low cost of operation (Zirath et al, 2017 ). Chaemsaithong et al ( 2015 ) compared the concentrations of IL-6 and IP-10 in amniotic fluid determined by standard enzyme-linked immunosorbent assay (ELISA) and a lateral flow-based immunoassay and reported that the results of the POC test strongly correlated with concentrations as determined by ELISA.…”
Section: Alternative Approaches As Potential Diagnostic Avenues For Tmentioning
confidence: 99%
“…Cooperation with automated machines is another research hotpot in POC fields. [67,68] A portable and automated Figure 7. The manipulation of liquids in microdevices.…”
Section: Manipulation Of Liquid Reagentsmentioning
confidence: 99%
“…Phospholipases A2 (PLA2) and sPLA2-IB 46,47 Lateral flow assay 46,47 Optical detection 46,47 Serum interleukin-8 (IL-8) 48 Microfluidic chip with magnetic beads Chemiluminescent assay Serum Typtophan 49 Aptamer-based Electrochemical biosensor Serum, saliva and urine Anticoagulants, unfractionated herapin and low molecular weight herapin 50…”
Section: Serummentioning
confidence: 99%